PERAN MOSALAKI SEBAGAI PEMIMPIN MASYARAKAT ADAT DALAM MELESTARIKAN BUDAYA DEMOKRASI (KULA KAME) PADA MASYARAKAT ADAT LIO DI KABUPATEN SIKKA - Fina Ndoa; Gisela Nuwa; Abdul Rodja Natsir (Universitas Tanjungpura, 2022)
This study aims to determine the role of Mosalaki as a traditional leader in preserving the democratic culture (kula kame) in the Lio indigenous people and to find out what are the obstacles to Mosalaki in preserving the democratic culture (kula kame) in the Lio indigenous people. This study uses qualitative research with an ethnographic approach and the data sources used are primary and secondary data. The results showed that the role of Mosalaki as a traditional leader of the Lio community, namely: controlling ulayat land, leading traditional rituals, and resolving conflicts in the community, while for Mosalaki's obstacles in preserving democratic culture (kula kame) the implementation of the traditional ritual itself, namely: internal barriers (internal). ), obstacles from outside (external), past and present leadership, and leadership insight itself.